Insights into RNA polymerase catalysis and adaptive evolution gained from mutational analysis of a locus conferring rifampicin resistance. Issue 19 (25th September 2017) - Yurieva, Olga; Nikiforov, Vadim; Nikiforov, Vadim; O'Donnell, Michael; Mustaev, Arkady
Abstract: S531 of Escherichia coli RNA polymerase (RNAP) β subunit is a part of RNA binding domain in transcription complex. While highly conserved, S531 is not involved in interactions within the transcription complex as suggested by X-ray analysis. To understand the basis for S531 conservation we performed systematic mutagenesis of this residue. We find that the most of the mutations significantly decreased initiation-to-elongation transition by RNAP. Surprisingly, some changes enhanced the production of full-size transcripts by suppressing abortive loss of short RNAs. S531-R increased transcript retention by establishing a salt bridge with RNA, thereby explaining the R substitution at the equivalent position in extremophilic organisms, in which short RNAs retention is likely to be an issue. Generally, the substitutions had the same effect on bacterial doubling time when measured at 20°. Raising growth temperature to 37° ablated the positive influence of some mutations on the growth rate in contrast to their in vitro action, reflecting secondary effects of cellular environment on transcription and complex involvement of 531 locus in the cell biology. The properties of generated RNAP variants revealed an RNA/protein interaction network that is crucial for transcription, thereby explaining the details of initiation-to-elongation transition on atomic level.